Prospects of the development of the halal products industry towards Indonesia's economic growth - Rosana, Ula Rochmatannia (Journal of Halal Product and Research (JHPR), 2024)
By being crowned as the largest Muslim population in the world, Indonesia actually has no small potential for the development of the halal and sharia industry. It can also be seen where the global trade business is currently, halal products are dominating. However, the potential for the development of the Indonesian halal industry has not been matched by good achievements at the global or international level. However, this is not an obstacle for Indonesia's development to advance a country's economy. Halal products are rahmatan lil alamin for those who use, consume, and those involved in them. This can make Indonesia play an important role in the development of the halal product industry, considering the large number of Muslim communities in Indonesia. With encouragement, government support, and hard work to revive the halal product industry in Indonesia, we can grow the domestic halal product industry. So this requires the right strategy for the development of the Indonesian halal product industry.